PENGARUH AKUNTANSI PERTANGGUNGJAWABAN, PROFESIONALISME, DAN JOB RELEVANT INFORMATION TERHADAP KINERJA MANAJERIAL - I Gusti Ayu Ari Wijayanti (UNHI Press, 2021)
Managerial performance is very important in running a good government. Some factors that affect managerial performance are responsibility accounting, professionalism, and job relevant information. This study aims to determine the effect of responsibility accounting, professionalism, and job relevant information on managerial performance in the Regional Apparatus Organization of Denpasar City. The population of this study was 33 service offices as many as 3.953 people, with a sample of 118 people. The method of determining the sample using purposive sampling method. Data obtained from questionnaires and analyzed using Multiple Linear Regression analysis. The results of this study indicate that responsibility accounting, professionalism, and job relevant information have a positive effect on managerial performance in the Regional Apparatus Organization of Denpasar City. This shows the better accounting responsibility, professionalism, and job relevant information, the managerial performance will be better.